EVpedia: a community web portal for extracellular vesicles research. (10th November 2014) - Kim, Dae-Kyum; Lee, Jaewook; Kim, Sae Rom; Choi, Dong-Sic; Yoon, Yae Jin; Kim, Ji Hyun; Go, Gyeongyun; Nhung, Dinh; Hong, Kahye; Jang, Su Chul; Kim, Si-Hyun; Park, Kyong-Su; et al.
Abstract : Motivation: Extracellular vesicles (EVs) are spherical bilayered proteolipids, harboring various bioactive molecules. Due to the complexity of the vesicular nomenclatures and components, online searches for EV-related publications and vesicular components are currently challenging. Results: We present an improved version of EVpedia, a public database for EVs research. This community web portal contains a database of publications and vesicular components, identification of orthologous vesicular components, bioinformatic tools and a personalized function. EVpedia includes 6879 publications, 172 080 vesicular components from 263 high-throughput datasets, and has been accessed more than 65 000 times from more than 750 cities. In addition, about 350 members from 73 international research groups have participated in developing EVpedia. This free web-based database might serve as a useful resource to stimulate the emerging field of EV research. Availability and implementation: The web site was implemented in PHP, Java, MySQL and Apache, and is freely available at http://evpedia.info . Contact: ysgho@postech.ac.kr